2020
DOI: 10.1016/j.jid.2019.08.449
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application of a Mast Cell Stabilizer Improves Impaired Diabetic Wound Healing

Abstract: Impaired wound healing in the diabetic foot is a major problem often leading to amputation. Mast cells have been shown to regulate wound healing in diabetes. We developed an indole-carboxamide type mast cell stabilizer, MCS-01, which proved to be an effective mast cell degranulation inhibitor in vitro and can be delivered topically for prolonged periods through controlled release by specifically designed alginate bandages. In diabetic mice, both pre-and post-wounding, topical MCS-01 application accelerated wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…Single-cell RNA sequencing analysis of 6154 cells from wounded and unwounded mouse skin revealed that MCS-01 primarily altered the gene expression of MCs, monocytes, and keratinocytes, while fibroblasts, adipocytes, and T cells had no significant changes. All the above suggests that topical MC stabilization can be a potentially successful treatment for DFUs [ 95 ].
Fig.
…”
Section: Mcs-related Diabetic Wound Therapymentioning
confidence: 99%
“…Single-cell RNA sequencing analysis of 6154 cells from wounded and unwounded mouse skin revealed that MCS-01 primarily altered the gene expression of MCs, monocytes, and keratinocytes, while fibroblasts, adipocytes, and T cells had no significant changes. All the above suggests that topical MC stabilization can be a potentially successful treatment for DFUs [ 95 ].
Fig.
…”
Section: Mcs-related Diabetic Wound Therapymentioning
confidence: 99%
“…Wound healing is a complicated biological processes, involving the spatial and temporal synchronization of various cells and cytokines, with a distinct pattern in inflammatory, proliferative and remodeling phases ( Tellechea et al, 2019 ). Deficiencies of homeostasis in the local microenvironment, including alterations in local physical forces, oxygen content, chemokines secretion and extracellular matrix remodeling, leads to impaired wound healing ( Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using CellMatch, we annotated clusters based on evidence-based score by matching the identified potential marker genes with known cell markers in tissue-specific cell taxonomy reference databases 48 . Also, we used cell marker genes from recent scRNA-seq studies of skin 17,28 - to identify the remining cell types. This allows us to identify the major skin cell types (Fig 5a).…”
Section: Resultsmentioning
confidence: 99%